Teacher sentiments about physical appearance and risk of bullying victimization: the mediating role of quality of student–teacher relationships and psychological adjustment - Longobardi, Claudio; Mastrokoukou, Sofia; Fabris, Matteo A. (Frontiers in Education, 2023)
Introduction: This study investigated the relationship between teachers' sentiments about physical appearance, student-teacher relationships, psychological adjustment, and the risk of becoming a victim of bullying. Method: Participants consisted of 995 students (471 females, 47.3%; Mage = 11.3, SDage = 1.49) and 64 teachers (56 females, 87.5%; Mage = 47.59). Students reported their levels of psychological adjustment and their involvement with bullying victimization, while teachers rated relationship quality with their students and reported their sentiments about students' physical appearance. Teachers' sentiments about physical appearance were analyzed using the NRC Emotion Lexicon. Correlation and mediation analyses were conducted with Mplus, using a multicategorical antecedent. Results: Results indicate that teachers' positive ratings of students' physical appearance were correlated with close teacher-student relationships, less conflictual relationships, whereas negative ratings were correlated with more conflictual student-teacher relationships and increased bullying victimization risk. Psychological adjustment mediated the relationship, with positive adjustment associated with closer relationships and negative adjustment associated with more conflict. Discussion: This study suggests the importance of teachers' sentiments about students' physical appearance. Positive sentiments promote supportive relationships and reduce the risk of bullying victimization, while negative sentiments erano correlate ad una relazione studente-insegnante netagativa and increased risk of bullying victimization. Promoting positive interactions between teachers and students and addressing appearance biases are critical to creating inclusive educational environments. Further research should focus on understanding and examining the impact of teacher attitudes on student well-being and bullying dynamics.